Implementasi Sistem Room Reservation Berbasis Web dengan PHPRad - Candra Gudiato; Mira Mira; Yuliana Yuliana; Santi Thomas (JURNAL TEKNIK KOMPUTER AMIK BSI, 2023)
Abstract - The Shanti Bhuana Institute is one of the colleges in the Bengkayang. The campus, which was founded in 2016, is now getting busier, both because of the increasing number of students from year to year, as well as the number of employees working there. This raises problems, one of which is related to the reservation (borrowing) of several rooms that can be used freely, both for lectures and meetings. Previously, recording room reservations was still done manually using paper. In addition, recording reservations is also not flexible because someone must to go to an authorized employee to record reservations. To adapt to the challenges of the digital era and the green economy, it is necessary to reduce the use of paper (paperless) by building a website-based room reservation system where users can make reservations that can be accessed in real-time anytime and anywhere. The research method used will apply the principle of object oriented programming. The system was built using the PHPRad framework with system implementation carried out at the Shanti Bhuana Institute. System implementation went well with a total of 5 rooms that could be reserved and 168 reservations had occurred since the system was implemented.